2022
DOI: 10.3389/fimmu.2022.904632
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss as the Main Clinical Presentation in NLRP3-Associated Autoinflammatory Disease

Abstract: The NLRP3 gene mutations are the cause of autosomal dominant autoinflammatory disorders (NLRP3-AID). Recently, hearing loss (HL) has been found to be the sole or major manifestation of NLRP3-AID. Here, we tested 110 autosomal dominant HL families with a custom panel of 237 HL genes and found one family carrying the NLRP3 c.1872C>G, p.Ser624Arg mutation. Functional studies revealed that this novel variant is a gain of function mutation, leading to increased activity of caspase-1 and subsequent oversecret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…21 In addition, based on previous reports of cochlear autoinflammation and hearing loss in affected individuals harboring NLRP3 missense mutations (p.Ser624Arg and p.Arg918Gln), the p.Gly571Val mutation could be associated with the early onset hearing loss in the individual who we report. 22,23 NLRP3 mutations lead to unregulated activation of the NLRP3 inflammasome, resulting in overproduction of inflammatory signals, such as interleukin-1. 9 Subsequent corneal inflammation may lead to corneal stromal opacification and scarring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In addition, based on previous reports of cochlear autoinflammation and hearing loss in affected individuals harboring NLRP3 missense mutations (p.Ser624Arg and p.Arg918Gln), the p.Gly571Val mutation could be associated with the early onset hearing loss in the individual who we report. 22,23 NLRP3 mutations lead to unregulated activation of the NLRP3 inflammasome, resulting in overproduction of inflammatory signals, such as interleukin-1. 9 Subsequent corneal inflammation may lead to corneal stromal opacification and scarring.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, based on previous reports of cochlear autoinflammation and hearing loss in affected individuals harboring NLRP3 missense mutations (p.Ser624Arg and p.Arg918Gln), the p.Gly571Val mutation could be associated with the early onset hearing loss in the individual who we report. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…[54,55] In addition, hereditary hearing loss has recently been associated with inflammation. [56][57][58] While the pathogenesis of SNHL is unclear and incomplete, inflammation is a critical component in the pathogenesis of many SNHLs. Understanding the role of inflammatory factors and their associated pathways in the pathologic activity of inner ear diseases is critical for studying their disease mechanisms.…”
Section: Other Snhlsmentioning
confidence: 99%
“…Studies have shown that NF‐κB is activated by cochlear radiation and reaches its maximum activation state after 2–6 h. Tetramethylpyridine has anti‐inflammatory and anticoagulant effects that protect against radiation‐induced ototoxicity [54,55] . In addition, hereditary hearing loss has recently been associated with inflammation [56–58] …”
Section: Snhl and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation